77 EXPERIENCES OF OLDER PEOPLE AND CARERS REFERRED TO AMBULATORY OUTREACH TEAM WITHIN INTEGRATED CARE PROGRAMME FOR OLDER PERSONS (ICPOP) SERVICE. (25th October 2022) - Akhtar, A; Lawlor, R; Cahalane, J; Gillman, C; Cronin, F; Daly, B; Hennessy, J; Naughton, C
Abstract: Background: Ambulatory outreach services are part of new pathways to reduce reliance on secondary care as outlined in the Integrated Care Programme for Older Persons. Multidisciplinary outreach teams provide urgent medical and rehabilitation services in the person's home to stabilise a health crisis. Methods: The study aimed to explore the experiences of older people accessing a ambulatory outreach service and identify development opportunities. Interpretive description, an inductive analytic approach, was used to seek an understanding of clinical phenomena that illuminate their characteristics, patterns and structure. Data collection used qualitative telephone interviews. A purposeful sample of older people and carers were recruited following discharge from the outreach service over a three-month period. Results: Sixteen participants (patients n=9 and carers n=7) were interviewed, 77% were female with a mean age of 83 years. Three major themes and seven sub-themes were identified: Theme 1: Gratitude for specialised care: a) Moment of crisis "It was absolutely brilliant"; b) Care in my home: physical and psychological benefits Theme 2: Living with and managing complexity: c) Resilience and resignation: living in the moment "Well she's doing good at the moment, God forbids if there is more injuries", d) Work of patients: maintain motivation & control; task and service boundaries e) Work of Families "We're doing it so far". Theme 3:Scope for pro-active planning & Integration: f) What happens next? an unpredictable future; h) Integration with GP & community, g) Unspoken plan- sub-conscious advanced care planning "Nobody makes the decision on their own they call someone else" Conclusion: The Outreach Team was highly valued by participants and was seen as vital in regaining functional capability and confidence to cope. Future developments need to examine task and service boundaries that undermine resilience, post outreach follow-up, integration with primary care, and opportunities for advanced care conversations.